(untitled) (Research, Society and Development, 2021)
Objective: Develop a systematic literature review analysing the sleep quality of health professionals on night shift. Method: A systematic literature review was carried out, with search in the electronic databases PubMed, Virtual Health Library, SCIELO. Studies that addressed the quality of sleep of health professionals who work on a night shift were included; published from 2016 to 2021 and made available in the databases, in English and Portuguese; whose participants were over 18 years of age. Review articles were excluded; articles whose participants were not health professionals and those who had a previous diagnosis of sleep disorders. Results: Of the total of 3,540 works found in the electronic databases, 26 were related to Scielo, 1,523 were found in PubMed, and 1,991 in the VHL (Virtual Health Library). 3,464 articles were excluded, from the 76 selected studies, and a manual search was performed, totaling 21 articles. Discussion: Excessive activities and long working hours, in addition to sleep disorders, can directly contribute to the problems that affect the social, psychological, and physiological life of health workers on night shifts, negatively affecting not only the professionals but also the work environment, the team and the patients themselves. Conclusion: The professionals who suffer the most daily conflicts in their workdays are those who perform them on a night shift in hospital, but they can obtain relief from the consequences through the elaboration of alternative scales.